Stability of the fcc phase in shocked nickel up to 332 GPa - Kimberly A. Pereira; Samantha M. Clarke; Saransh Singh; Richard Briggs; Christopher P. McGuire; Hae Ja Lee; Dimitri Khaghani; Bob Nagler; Eric Galtier; Eric Cunningham; David McGonegle; Sally J. Tracy; et al. (Nature Communications)
Abstract Despite making up 5-20 wt.% of Earth’s predominantly iron core, the melting properties of elemental nickel at core conditions remain poorly understood, due largely to a dearth of experimental data. We present here an in situ X-ray diffraction study performed on laser shock-compressed samples of bulk nickel, reaching pressures up to  ~ 500 GPa. Hugoniot states of nickel were targeted using a flat-top laser drive, with in situ X-ray diffraction data collected using the Linac Coherent Light Source. Rietveld methods were used to determine the densities of the shocked states from the measured diffraction data, while peak pressures were determined using a combination of measured particle velocities, shock transit times, hydrodynamic simulations, and laser intensity calibrations. We observed solid compressed face-centered cubic (fcc) Ni up to at least 332 ± 30 GPa along the Hugoniot—significantly higher than expected from the majority of melt lines that have been proposed for nickel. We also bracket the partial melting onset to between 377 ± 38 GPa and 486 ± 35 GPa.